Ballet class: its development in early childhood education in times of the covid-19 pandemic- An experience report: O SEU DESENVOLVIMENTO NA EDUCAÇÃO INFANTIL DURANTE A PANDEMIA DO COVID-19- UM RELATO DE EXPERIÊNCIA (Fiep Bulletin - online, 2025)
Due to the worsening of the COVID-19 pandemic, the population had to adapt to the new scenario, where schools, extracurricular activities, and other departments began to conduct their activities online. Ballet was no exception, and during this period, some difficulties were encountered and promptly resolved. This paper presents the experiential account of a children's ballet teacher during the 2020 pandemic. Due to the scarcity of works in this area, this study aims to clarify the process of conducting classes in case of future pandemics or situations where in- person classes are not feasible. In addition to the experiential account, an integrative review was conducted to provide a foundation for the research. During the data collection for this work, five articles from the Virtual Health Library (BVS) and four articles from Scielo were included, covering the relevant thematic aspects. It was concluded that playful ballet classes can serve as a means to re-engage students in lessons, and remote formats can be employed in cases where in-person meetings are not possible for any reason.
Keywords: playfulness; creativity; children's ballet; remote classes; experiential account